Could this be Australia’s rarest Banksia? Banksia vincentia (Proteaceae), a new species known from fourteen plants from south-eastern New South Wales, Australia - Stimpson, Margaret Leith; Bruhl, Jeremy J.; Weston, Peter H. (Phytotaxa, 2014)
Possession of hooked, distinctively discolorous styles, a broadly flabellate common bract subtending each flower pair, and a lignotuber place a putative new species, Banksia sp. Jervis Bay, in the B. spinulosa complex. Phenetic analysis of individuals from all named taxa in the B. spinulosa complex, including B. sp. Jervis Bay, based on leaf, floral, seed and bract characters support recognition of this species, which is described here as Banksia vincentia M.L.Stimpson & P.H.Weston. Known only from fourteen individuals, B. vincentia is distinguished by its semi-prostrate habit, with basally prostrate, distally ascending branches from the lignotuber, and distinctive perianth colouring. Its geographical location and ecological niche also separate it from its most similar congeners.